Growth and Nitrogen Uptake by Potato and Cassava Crops Can Be Improved by Azospirillum brasilense Inoculation and Nitrogen Fertilization - Fernandes, Adalton Mazetti [UNESP]; da Silva, Jessica Aparecida [UNESP]; Eburneo, Juliana Aparecida Marques [UNESP]; Leonel, Magali [UNESP]; Garreto, Francisca Gyslane de Sousa [UNESP]; Nunes, Jason Geter da Silva [UNESP] (MDPI, 2023)
Nitrogen (N) is the nutrient most taken up by potato and cassava crops and Azospirillum brasilense may contribute to the growth of these crops. Pot experiments evaluated A. brasilense and mineral N application on leaf N concentration, plant growth, and N uptake by potato and cassava grown under natural and disinfected soil. The rates of 2.8 × 108 colony-forming units mL−1 of A. brasilense combined with 0, 75, 150, and 300 mg dm−3 N or 0, 50, 100, and 200 mg dm−3 N were used for potato or cassava grown. At low N supply in natural soil, A. brasilense inoculation increased N concentration in potato leaves by 23–38%, without benefits to plant growth or N uptake. At unfertilized N treatments of both soils, A. brasilense inoculation increased cassava leaf N concentration by 25–33%, but an 11–32% increase in shoot biomass occurred in treatments inoculated and N supplied. Potato crops responded positively to mineral N supply, but cassava responded to fertilization only in disinfected soil. In disinfected soil fertilized with N, A. brasilense inoculation increased cassava N uptake by 27–40%. In contrast, in natural soil, A. brasilense minimized the negative effect of N excess on the tuber development of cassava. These results show that the use of A. brasilense is a more interesting alternative to improve N status and growth in cassava than in potatoes.
Keywords: growth-promoting bacteria; nitrogen fixation; tuber crops